Socioeconomic and environmental determinants and hypovitaminosis D in adolescents in the northeast of Brazil: a hierarchical approach (Research, Society and Development, 2022)
Family socioeconomic and environmental conditions are associated with health status and disease outcomes in infancy, acting at different levels of determination over these events, positively or negatively affecting individuals. Methods was adopted a hierarchical approach to investigate a vitamin D insufficiency and socioecomimc determinants in the basic, intermediate, and immediate levels. The logistic regression and odds ratio (OR) as an association measure were used to assess the relationship of interest. The prevalence of vitamin D insufficiency (10-29.9 ng/ml) was 54.1% of the adolescents, no vitamin D deficiency (